International Open Trial of Uniform Multi-Drug Therapy Regimen for 6 Months for All Types of Leprosy Patients : Rationale, Design and Preliminary Results - Kroger, A.; Pannikar, V.; Htoon, M. T.; Jamesh, A.; Katoch, K.; Krishnamurthy, P.; Ramalingam, K.; Jianping, S.; Jadhav, V.; Gupte, M. D.; Manickam, P. (2012)
OBJECTIVE: To describe the rationale, design and preliminary results of an open trial of 6 months uniform multi-drug therapy (U-MDT) for all types of leprosy patients assuming a cumulative relapse rate not exceeding 5% over 5 years of follow-up. METHODS: We intended to recruit 2500 patients each in multi-bacillary (MB) and pauci-bacillary (PB) groups from India (five centres) and China (two centres). Standardized clinical criteria were used to assess skin lesions in the field. RESULTS: A total of 2912 patients enrolled from November 2003 to May 2007 (India, 2746; China, 166). MB patients constituted 39% and 3% had grade 2 disability. During follow-up, 27 patients (0.9%) developed new lesions. Of these, 78% were on account of reactions. Six patients had clinically confirmed relapse. Clofazimine-related skin pigmentation was short-lived and was acceptable to patients. We analysed data for clinical status of skin lesions. About 2.9% of patients were lost to follow-up; 85.9% completed treatment, of whom 19% had inactive skin lesions. PB patients responded better than MB patients (27%vs. 6%; P < 0.001). At the end of the first (n = 2013) and second year (n = 807) of follow-up post-U-MDT, in 49% and 46% patients, lesions were inactive, respectively (59% and 57% in PB, 37% and 28% in MB; P < 0.001). CONCLUSION: U-MDT appears to be promising with respect to clinical status of skin lesions.